Fake Anthropological Keywords - Jackson, Jr, John L. (HAU Books, 2018)
Fakes, forgery, counterfeits, hoaxes, bullshit, frauds, knock offs-such terms speak, ostensibly, to the inverse of truth or the obverse of authenticity and sincerity. But what does the modern human obsession with fabrications and frauds tell us about ourselves? And what can anthropology tell us about this obsession? This timely book is the product of the first Annual Debate of Anthropological Keywords, a collaborative project between HAU, the American Ethnological Society, and L'Homme, held each year at the American Anthropological Association Meetings. The aim of the debate is reflect critically on keywords and terms that play a pivotal and timely role in discussions of different cultures and societies, and of the relations between them. This book, with multiple authors, explodes open our common sense notions of "novelty," "originality," and "truth," questioning how cultures where deception and mistrust flourish seem to produce effective, albeit opaque, forms of sociality.